Aram Dorsum: An Extensive Mid‐Noachian Age Fluvial Depositional System in Arabia Terra, Mars. Issue 5 (6th May 2020) - Balme, Matthew R.; Gupta, Sanjeev; Davis, Joel M.; Fawdon, Peter; Grindrod, Peter M.; Bridges, John C.; Sefton‐Nash, Elliot; Williams, Rebecca M. E.
Abstract: A major debate in Mars science is the nature of the early Mars climate, and the availability of precipitation and runoff. Observations of relict erosional valley networks have been proposed as evidence for extensive surface runoff around the Noachian‐Hesperian boundary. However, these valley networks only provide a time‐integrated record of landscape evolution, and thus, the timing, relative timescales and intensity of aqueous activity required to erode the valleys remain unknown. Here, we investigate an ancient fluvial sedimentary system in western Arabia Terra, now preserved in positive relief. This ridge, "Aram Dorsum, " is flat‐topped, branching, 85 km long, and particularly well preserved. We show that Aram Dorsum was an aggradational alluvial system and that the existing ridge was once a large river channel belt set in extensive flood plains, many of which are still preserved. Smaller, palaeochannel belts feed the main system; their setting and network pattern suggest a distributed source of water. The alluvial succession is up to 60 m thick, suggesting a formation time of 10 5 to 10 7 years by analogy to Earth. Our observations are consistent with Aram Dorsum having formed by long‐lived flows of water, sourced both locally, and regionally as part of a wider alluvial system in Arabia Terra. This suggests frequent or seasonal precipitation as the source of water. Correlating our observations with previous regional‐scale mapping shows that Aram Dorsum formed in the mid‐Noachian. Aram Dorsum is one of the oldest fluvial systems described on Mars and indicates climatic conditions that sustained surface river flows on early Mars. Plain Language Summary: The oldest regions of Mars contain ancient valleys, carved by running water, and sinuous ridges, often interpreted as the remnants of former riverbeds, left upstanding by erosion. These "inverted channel" systems provide insight into Mars's ancient climate and hydrologic cycle. We use high‐resolution satellite images to investigate "Aram Dorsum, " an 85 km long ridge system in the Arabia Terra region. Our observations show that Aram Dorsum is composed of sedimentary rocks, originally deposited in rivers or their adjacent floodplains. The Aram Dorsum sedimentary material is up to 60 m thick, which, by comparison with similar sedimentary deposits on Earth, suggests that the Aram Dorsum river system was active for between 10, 000 and 10 million years. Our study also indicates that Aram Dorsum was formed around 3.9 billion years ago, an age consistent with other evidence for ancient rivers and lakes in this region. The water that flowed within the rivers at Aram Dorsum probably came from both locally and regionally generated rainfall or snowfall, rather than a single point source of water, such as large distant ice sheets. Our observations therefore point to an ancient Martian climate that supported precipitation and river flow for thousands or millions of years. Key Points: Aram Dorsum (AD) is an 85 km long, branching, flat‐topped ridge with layered flanks in Arabia Terra, Mars AD is an exhumed aggradational river system with floodplains deposits and was probably active for 10 5 –10 7 years in the mid‐Noachian The AD rivers were sourced both locally and regionally, indicating that the ancient Martian climate supported precipitation and runoff here